Two new species of feather mites (Acarina: Psoroptidia) from the blue-throated blue flycatcher, Cyornis rubeculoides (Passeriformes: Muscicapidae). Issue 5 (9th February 2017) - Constantinescu, I.C.; Cobzaru, I.; Geamana, N.A.; Mukhim, D.K.B.; Adam, C.
ABSTRACT: The paper describes two new species of feather mites collected from the blue-throated blue flycatcher Cyornis rubeculoides (Vigors) (Passeriformes: Muscicapidae) in India (Meghalaya): Trouessartia kharkhanensis Constantinescu et al. sp. nov. (Trouessartiidae) and Proterothrix cyornissimilis Constantinescu et al. sp. nov. (Proctophyllodidae: Pterodectinae). Both sexes of T. kharkhanensis differ from the closest species, T. rubecula Jablonska, 1968 by having setae si and c2 lanceolate and setae c3 and sR III with acute apex. In males of the new species, the adanal apodemes have a hook-like retroverse apophysis and the internal margins of terminal lamellae have a shallow invagination at the level of setae h3 . Both sexes of P. cyornissimilis differ from the closest species, P. cyornis Mironov and Tolstenkov, 2013, mainly by the ornamentation of the dorsal shields: it is absent on the prodorsal shield and poorly expressed on the hysteronothal shield. In males of the new species, the supranal concavity is triangular and the genital arch has a pair of small ovoid sclerites at its tips. http:/zoobank.org/urn:lsid:zoobank.org:pub:1671D6D4-8895-467B-A124-05EDBB0DF406